2015
DOI: 10.1038/nmat4448
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced energy transport in genetically engineered excitonic networks

Abstract: One of the challenges for achieving efficient exciton transport in solar energy conversion systems is precise structural control of the light-harvesting building blocks. Here, we create a tunable material consisting of a connected chromophore network on an ordered biological virus template. Using genetic engineering, we establish a link between the inter-chromophoric distances and emerging transport properties. The combination of spectroscopy measurements and dynamic modelling enables us to elucidate quantum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
101
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 34 publications
1
101
0
Order By: Relevance
“…4 Recent studies, however, have shown that an efficient singlet exciton migration can occur in highly ordered supramolecular materials. [6][7][8] In particular, Sung et al. have shown by ultrafast transient fluorescence spectroscopy that in helical π-stacks of perylene bisimides delocalized excitons are initially formed and move coherently along the chain in tens of femtoseconds prior to the excimer formation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Recent studies, however, have shown that an efficient singlet exciton migration can occur in highly ordered supramolecular materials. [6][7][8] In particular, Sung et al. have shown by ultrafast transient fluorescence spectroscopy that in helical π-stacks of perylene bisimides delocalized excitons are initially formed and move coherently along the chain in tens of femtoseconds prior to the excimer formation.…”
Section: Introductionmentioning
confidence: 99%
“…7 Heechul et al have obtained a tunable light-harvesting material, based on a selfassembled chromophore network controlled by a genetically-engineered virus template, which has exhibited enhanced exciton transport via a partially coherent regime. 8 These recent examples clearly highlight the growing interest for obtaining controllable molecular materials for potential nanophotonic and quantum information applications where excitons move beyond the incoherent transport regime. In this sense, it would be 3 useful to consider model systems for studying partially coherent exciton propagation with a good level of detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After a time τ decoh = γ −1 the histories are fully decohered. Indeed, due to the specific model of decoherence (11), which amounts to projective measurements on |i i| at each site with a rate γ , the system kills the coherence in the site basis, which in turn corresponds to the stable pointer basis for this model [7], i.e., the basis in which the density matrix is forced to be diagonal by the specific decoherence model. On the other hand, and for the same reason, the dynamics starts to build up coherence in the exciton basis |E i E i | [see Fig.…”
Section: Trimermentioning
confidence: 99%
“…There is now an emerging consensus that efficient transport in natural and biologically inspired artificial light-harvesting systems builds on a finely tuned balance of quantum coherence and decoherence caused by environmental noise [9][10][11][12][13], a phenomenon known as environment-assisted quantum transport (ENAQT). This paradigm has emerged with clarity in recent years, as modern spectroscopic techniques first suggested that exciton transport within photosynthetic complexes might be coherent over appreciable time scales [14].…”
Section: Introductionmentioning
confidence: 99%